Three hundred years of death : the Egyptian funerary industry in the Ptolemaic period - Cannata, Maria (Culture and History of the Ancient Near East, 2020)
"In Three Thousand Years of Death, The Egyptian Funerary Industry in the Ptolemaic Period, Maria Cannata provides a detailed survey of the organisation of the necropolises and the funerary workers, as well as their role in the practical aspects of the mummification, funeral, burial, and mortuary cult of the deceased, in Ptolemaic Egypt (332-30 BC). The author gathers together and synthesises hundreds of the original textual sources, as well as the relevant archaeological sources, on the organisation of the funerary industry and its practitioners, revealing important regional and chronological variations overlooked in studies focusing on a limited geographical area, a shorter timeframe, or a smaller group of documents".